Manajemen Pembelajaran Santri Pemalu di MA Tafaqquh Anwaha - Syahrani, Syahrani; Mahelda, Desi; Hairiati, Hairiati; Salsabilla, Salsabilla; Azizah, Siti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Each student has different characteristics, including shyness, which can affect the learning process. This study aims to analyze the management of learning for shy students at MA Tafaqquh Anwaha by examining various aspects, such as the characteristics of shy students, strategies to overcome shyness, and the roles of parents and teachers in helping students become more confident. This research uses a qualitative approach with a case study method. The findings indicate that shy students tend to have a fear of interaction, lack self-confidence, and are reluctant to participate actively in learning. To address this issue, specific strategies are needed, such as creating a comfortable learning environment, providing motivation, and gradually involving students in group activities. Moreover, parents play a crucial role in providing emotional support and building children's confidence at home. Teachers also serve as facilitators who can create an inclusive learning atmosphere, provide positive encouragement, and apply interactive teaching methods to help shy students become more engaged in the learning process. With proper learning management, shy students can develop both academically and socially, enabling them to adapt to the school and community environment.